2023
DOI: 10.1093/g3journal/jkad096
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptional cofactor regulatory network for the C. elegans intestine

Abstract: Chromatin modifiers and transcriptional cofactors (collectively referred to as CFs) work with DNA-binding transcription factors (TFs) to regulate gene expression. In multicellular eukaryotes, distinct tissues each execute their own gene expression program for accurate differentiation and subsequent functionality. While the function of TFs in differential gene expression has been studied in detail in many systems, the contribution of CFs has remained less explored. Here, we uncovered the contributions of CFs to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…In agreement with our Gene Ontology analysis of eat-2 expression changes, we found a substantial and significant set of downregulated genes in eat-2 mutant animals to be enriched in sperm, as well as significant over-representation of muscle-associated genes. The intestine is commonly referred to as the most metabolically active tissue in C. elegans, and both the MML-1::MXL-2 complex and PHA-4 act in intestinal cells in adult animals (Panowski et al 2007;Johnson et al 2014;Nakamura et al 2016;Horowitz et al 2023); we found enrichment for intestinally expressed genes in both the up-and down-regulated transcriptional response to eat-2, mxl-2, or pha-4 single-perturbation conditions. Intriguingly, we found enrichment of neuron-associated genes among those down-regulated in mxl-2 null mutant animals, which suggests Myc-family TFs may coordinate organismal adaptive responses from the nervous system.…”
Section: Mxl-2 Regulates Expression Of a Distinct Set Of Genes During...mentioning
confidence: 65%
“…In agreement with our Gene Ontology analysis of eat-2 expression changes, we found a substantial and significant set of downregulated genes in eat-2 mutant animals to be enriched in sperm, as well as significant over-representation of muscle-associated genes. The intestine is commonly referred to as the most metabolically active tissue in C. elegans, and both the MML-1::MXL-2 complex and PHA-4 act in intestinal cells in adult animals (Panowski et al 2007;Johnson et al 2014;Nakamura et al 2016;Horowitz et al 2023); we found enrichment for intestinally expressed genes in both the up-and down-regulated transcriptional response to eat-2, mxl-2, or pha-4 single-perturbation conditions. Intriguingly, we found enrichment of neuron-associated genes among those down-regulated in mxl-2 null mutant animals, which suggests Myc-family TFs may coordinate organismal adaptive responses from the nervous system.…”
Section: Mxl-2 Regulates Expression Of a Distinct Set Of Genes During...mentioning
confidence: 65%